Mythri 1.0—Progress of an Indian Surgical Robot - V., Vikas; Voggu, Aravind Reddy; Arumalla, Kirit; Doshi, Ronak; Ramkumar, Aravind; Mahadevan, Anita; Rao, Madhav (Indian Journal of Neurosurgery, 2020)
Neurosurgical procedures are performed using operating microscopes. The technology of most microscopes has not changed much over the past 60 years. The National Institute of Mental Health and Neurosciences and International Institute of Information Technology based at Bengaluru have embarked on joint collaboration for developing robot for neurosurgical applications. As a working prototype, robotic microscope Mythri 1.0 has been developed. An overview of the development process, working, and features of the device is presented in the article.
Keywords: neurosurgical robot; Mythri 1.0; robotic microscope; neurosurgical microscope